Increased Placental sFLT1 (Soluble fms-Like Tyrosine Kinase Receptor-1) Drives the Antiangiogenic Profile of Maternal Serum Preceding Preeclampsia but Not Fetal Growth Restriction. Issue 2 (22nd July 2022) - Gaccioli, Francesca; Sovio, Ulla; Gong, Sungsam; Cook, Emma; Charnock-Jones, D. Stephen; Smith, Gordon C.S.
Abstract : Background: Preeclampsia and fetal growth restriction (FGR) are both associated with an increased ratio of sFLT1 (soluble fms-like tyrosine kinase-1) to PlGF (placenta growth factor) in maternal serum. In preeclampsia, it is assumed that increased placental release of sFLT1 results in PlGF being bound and inactivated. However, direct evidence for this model is incomplete, and it is unclear whether the same applies in FGR. Methods: We conducted a prospective cohort study where we followed 4212 women having first pregnancies from their dating ultrasound, obtained blood samples serially through the pregnancy, and performed systematic sampling of the placenta after delivery. The aim of the present study was to determine the relationship between protein levels of sFLT1 and PlGF in maternal serum measured at ≈36 weeks and placental tissue lysates obtained after term delivery in 82 women with preeclampsia, 50 women with FGR, and 132 controls. Results: The sFLT1:PlGF ratio was increased in both preeclampsia and FGR in both the placenta and maternal serum. However, in preeclampsia, the maternal serum ratio of sFLT1:PlGF was strongly associated with placental sFLT1 level (r=0.45; P <0.0001) but not placental PlGF level (r=−0.17; P =0.16). In contrast, in FGR, the maternal serum ratio of sFLT1:PlGF was strongly associated with placental PlGF level (r=−0.35; P =0.02) but not sFLT1 level (r=0.04; P =0.81). Conclusions: We conclude that the elevated sFLT1:PlGF ratio is primarily driven by increased placental sFLT1 in preeclampsia, whereas in FGR, it is primarily driven by decreased placental PlGF.